Analisis Kepadatan Lapisan Pondasi Agregat (LPA) Kelas A Dengan Menggunakan Metode Sand Cone Pembangunan Jalan Ruas Takkalasi – Bainange Lawo Di Kabupaten Soppeng - Ahmad Akbar; Hamka Hamka; Hendro Widarto; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Soil compaction is required to extend firmness, volume weight and diminish soil porousness at the extend area where adaptable asphalt framework will be built. The point of this inquire about is to decide the impact of soil thickness on street development utilizing the sandcone strategy and to decide the comparison of field compaction testing (Sand Cone) with research facility compaction testing (Compaction Testing) on the development of the Takkalasi-Bainange Lawo area of the Soppeng Rule street. This research was carried out within the Respectful Designing research facility of the Muhammadiyah College of Parepare for 4 months from Eminent to December 2023 utilizing the Sandcone test strategy compared to the compaction strategy. The comes about of the investigation of sandcone testing on soil thickness during the development of Jalan ruas takkalasi-bainange lawo within the locale soppeng, appeared that the thickness of dry soil within the gap was an normal of 2.368 gr/cc. and the comes about of the comparison of Field Compaction Testing (Sand Cone) with Research facility Testing (Compaction Testing) appeared that the most elevated degree of thickness was at STA 2 + 600 at 104.94 and the least degree of thickness was at STA 2 + 300 with a esteem of 101.24 and in case found the middle value of the thickness degree esteem is 101.383%. From the comes about gotten, it meets the Binamarga details, specifically a least of 90%, so the compaction on the development of the Takkalasi - Bainange Disoppeng street is classified as exceptionally compelling since it has met the least details